Prospects of medicinal herbs management in reclaimed minelands of Ukraine - Kharytonov, Mykola; Харитонов, Микола Миколайович; Babenko, M.; Бабенко, М.; Velychko, Oleksandr; Величко, Олександр Петрович; Pardini, G.; Пардіні, Г. (Мелітопольський державний педагогічний університет імені Богдана Хмельницького, 2018)
The rocks of Nikopol manganese ore basin are represented with Neogenic and Paleogenic sediments. After realization of the stage of mine-technical reclamation loess-like and red-brown loams appear on the dump surface. Taking into biological specialty of most species of medicinal herbs, it can be assuming, some of them need culture on the humus rich soil to form the feedstock of stable quality, others can be successfully grown on pour leached soils, generally known as loess-like loams coming on the surface. Numerous types of medicinal herbs were tested in situ on the reclaimed mine land. From the comparison of the results with the defined permissible concentration limits, it was concluded that the levels of trace element contents in the locally available medicinal plants under investigation fall around the permissible range except for German chamomile (Matricaria chamomilla), Dwarf everlast (Helichrysum arenarium), Motherwort (Leonurus cardiac) and St John's-wort (Hypericum perforatum) with regard to its extremely high Cu and Mn content. Породи Нікопольського марганцеворудного басейну представлені неогеновими та палеогеновими відкладами. Після проведення етапу гірничо-технічної рекультивації на поверхні відвалу з'являються лесоподібні та червоно-бурі суглинки. Беручи до уваги біологічну особливість більшості видів лікарських трав, можна припустити, що деякі з них потребують культури на багатому гумусом ґрунті для формування сировини стабільної якості, інші можуть успішно вирощуватися на вимиваних вилужених ґрунтах, зазвичай відомих як лесоподібні. суглинки, що виходять на поверхню. На рекультивованих землях шахти було випробувано численні види лікарських трав. З порівняння результатів із визначеними гранично допустимими концентраціями.
Перспективи використання лікарських трав на рекультивованих гірничих землях України
Keywords: reclaimed mine land; рекультивовані шахтні землі; medicinal herbs; лікарські трави; trace elements; розсіяні елементи